ECONOMIC EVALUATION OF GPS TECHNOLOGY IN SERBIAN AGRICULTURE - Marković, Dragan; Pokrajac, Slobodan; Simonović, Vojislav; Marković, Ivana (International Journal of Economic Practice and Policy, 2013)
This paper examined the level of savings in the application of the most modern technical systems for satellite guidance and control over performing agricultural operations throughout the season. The exemplary property was Agricultural Corporation Belgrade (PKB), which covers about 21.000 hectares of arable land. The effects of plot shape and direction of movement of tractor-attachment units in calculating the savings from reduced overlapping of adjacent passes were studied. The analysis was carried out of savings per crop (maize, wheat, soybean, sugar beet and alfalfa) and the operations for each crop separately, based on the manufacturing technology applied to an exemplary property. Detailed data are shown only for wheat and barley.Comparing the achieved level of savings, the application of guidance for the type of the most economically viable operations was found as well as the needed equipment level of guidance devices and management. In particular, the analysis involved the functional dependence of the economic savings in fuel and inputs for the operations such as mineral fertilizers distribution and chemical plant protection. Tabulated are the data estimates for the degree of anticipated savings for operations related to the five analyzed crops.
Keywords: wheat; precision farming; pass fitting; plot; fuel; inputs; savings